The use of picture dictionary to improve vocabulary of 5th year students, at unidad educative Marietta de Veintimilla of Loja city, during the academic period 2014-2015 - Castillo Quezada, Maria Elizabeth (2016)
The present research work had as objective to improve the English vocabulary of 5th year students at Unidad Educativa “Marieta de Veintimilla” of Loja city, during the academic period 2014-2015, through the application of picture dictionary. The methods used were the scientific, analytic-synthetic, descriptive and statistical, which contributed in each part of the process of the research work. To collect the data, tests and questionnaires were applied to thirty-two students. Also, observation sheets and field diary were used. The main result of the research showed that students improved their level in writing and pronouncing the words, and to use them correctly in different situations. The main conclusion of the research showed that the use of picture dictionary involved students in the process of vocabulary acquisition and in the active learning, which allowed them to increase their lexical and use English in common life situations.